2018
DOI: 10.1504/ijsmm.2018.10012843
|View full text |Cite
|
Sign up to set email alerts
|

Hashmoney: exploring Twitter hashtag use as a secondary ticket market price determinant

Abstract: The growth and prevalence of sport event ticket transactions on secondary ticket market platforms such as StubHub has led to the creation of a body of academic research studying this new phenomenon. Factors such as team performance and perceptions of fairness have been explored for their relationship with the price of secondary market tickets. This exploratory study introduces a new potential price determinant-social media activity-itself a popular online phenomenon that has inspired considerable academic rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The model was developed based on literature on the secondary ticket market (e.g. Drayer and Shapiro, 2009; O'Hallarn et al ., 2018; Shapiro et al ., 2021; Shapiro and Drayer, 2014). Additionally, ticket prices on each day were dummy coded to analyze how the number of days remaining affected listed ticket prices (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was developed based on literature on the secondary ticket market (e.g. Drayer and Shapiro, 2009; O'Hallarn et al ., 2018; Shapiro et al ., 2021; Shapiro and Drayer, 2014). Additionally, ticket prices on each day were dummy coded to analyze how the number of days remaining affected listed ticket prices (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed numerous price determinants in diverse secondary ticket market domains (e.g. seat location, team's current winning percentage, number of superstars, division/league affiliation, number of tweets and part of the season; Drayer et al ., 2012a; O'Hallarn et al ., 2018; Shapiro and Drayer, 2014; Shapiro et al ., 2016; Shapiro et al ., 2021). Price determinants have been discovered in a resale environment that is mostly driven by demand (Shapiro and Drayer, 2014).…”
Section: Introductionmentioning
confidence: 99%